Mitigation of Tax Aggressiveness through Good Corporate Governance Company’s Website and Corporate Social Responsibility Disclosure: Evidence-Concentrated Ownership Companies - Citrawati Jatiningrum; Fauzi; Linda Septarina (Universitas Negeri Semarang, 2024)
Purposes: This study aims to briefly prove the effect of Good Corporate Governance (GCG), the Company’s Website, and Corporate Social Responsibility Disclosure (CSRD) on tax aggressiveness. This study looks at businesses with a high ownership concentration level with the potential to expropriate minority ownership. Methods: Purposive judgment sampling with multiple regression analysis was applied to a sample of manufacturing companies listed on the Indonesia Stock Exchange. Findings: The findings reveal that GCG has a significant effect on Tax aggressiveness, while CSR disclosure activities also hurt tax aggressiveness. This evidence also proves that CSR activities carried out by the Company consistently reduce corporate tax aggressiveness. However, the Company’s website has no discernible impact on tax aggressiveness. Novelty: This study differs from previous studies because it considers Indonesia’s weak investor protection and concentrated ownership structures. There is a lack of prior studies on concentrated ownership companies and the relationship between good corporate governance, corporate social responsibility disclosure, and company websites on tax aggressiveness.